Creación de un centro estético y spa masculino en la ciudad de Guayaquil - Leon Barco, Carlos Eduardo (2009)
The aim of this study is to collect, analyze and infer all necessary information for the creation of the exclusive spa and aesthetic center for men in the city of Guayaquil, in order to cover the unmet demand that exists in the city. Because it is a new company, we will center our work in the implement of a marketing plan to seek the introduction of the company in an existing market with the information collected. The target of the project is specifically for men of upper middle and upper class. The company seeks to offer in these modern times a service aimed to satisfy the needs of relaxation that every time are higher due to stress caused by the abundant obligations and work responsibilities. The value of creating this project is that there is no a similar place that provides all the features that comprise this service and even less to propose a specially designed for men. The results were successful for the development of the project with the most important characteristics as economic feasibility and market acceptance.